2014
DOI: 10.1371/journal.pone.0104651
|View full text |Cite
|
Sign up to set email alerts
|

Genome Analysis of Bacillus amyloliquefaciens Subsp. plantarum UCMB5113: A Rhizobacterium That Improves Plant Growth and Stress Management

Abstract: The Bacillus amyloliquefaciens subsp. plantarum strain UCMB5113 is a Gram-positive rhizobacterium that can colonize plant roots and stimulate plant growth and defense based on unknown mechanisms. This reinforcement of plants may provide protection to various forms of biotic and abiotic stress. To determine the genetic traits involved in the mechanism of plant-bacteria association, the genome sequence of UCMB5113 was obtained by assembling paired-end Illumina reads. The assembled chromosome of 3,889,532 bp was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(84 citation statements)
references
References 58 publications
(63 reference statements)
3
78
1
2
Order By: Relevance
“…The main parameters used to sensitively and objectively determine the ability of the strains to affect the photosynthetic apparatus in plants are minimum fluorescence (F 0 ), maximum photochemical quantum yield of photosystem II (PSII) (F v /F m ), PSII operating efficiency (Φ PSII ), non-photochemical quenching (NPQ), and electron transport rate (ETR) (Lucas et al, 2014;García-Cristobal et al, 2015). Bacillus is one of the main rhizobacteria that has been used as a study model for understanding many processes, because it has been found to possess a wide genetic diversity adapted to different conditions and numerous properties of interest applied in industry, microbiology and agriculture (Niazi et al, 2014). Inoculation with B. subtilis increase photosynthesis in Arabidopsis through the modulation of plant endogenous sugar/abscisic acid (ABA) signaling, with a regulatory role for plant symbionts in photosynthesis (Zhang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The main parameters used to sensitively and objectively determine the ability of the strains to affect the photosynthetic apparatus in plants are minimum fluorescence (F 0 ), maximum photochemical quantum yield of photosystem II (PSII) (F v /F m ), PSII operating efficiency (Φ PSII ), non-photochemical quenching (NPQ), and electron transport rate (ETR) (Lucas et al, 2014;García-Cristobal et al, 2015). Bacillus is one of the main rhizobacteria that has been used as a study model for understanding many processes, because it has been found to possess a wide genetic diversity adapted to different conditions and numerous properties of interest applied in industry, microbiology and agriculture (Niazi et al, 2014). Inoculation with B. subtilis increase photosynthesis in Arabidopsis through the modulation of plant endogenous sugar/abscisic acid (ABA) signaling, with a regulatory role for plant symbionts in photosynthesis (Zhang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Through the antiSMASH 4.0 genome analysis tool (Blin et al, 2017), 30 clusters of secondary metabolites were identified in the genome of the JT3-1 strain: two transATPKS-NRPS, two transATPKS (trans-acyl transferase polyketide synthetase), one lantipeptide, one encoding NRPS (non-ribosomal peptide synthetase), one T3PKS, one bacteriocin-Nrps, two terpenes, one other KS, three Cf_fatty_acid, five Cf_saccharide, and 11 Cf_putative ( Table 3 ). Eight clusters were clearly involved in the synthesis of difficidin, surfactin, fengycin, butirosin, macrolactin, bacilysin, bacillaene and bacillibactin, and they were closely related with antimicrobial activities (Chen et al, 2009; Niazi et al, 2014; Ongena et al, 2005; Liu et al, 2017; Kim et al, 2017; Stein, 2005; Pandin et al, 2018). This analysis showed that at least 17% of the JT3-1 genome contributed to the transport and regulation of antibiotic biosynthesis.…”
Section: Secondary Metabolite Clustersmentioning
confidence: 99%
“…Besides producing many secondary metabolites with antimicrobial activity, several Bacillus spp. possess high secretory ability and some strains utilize ''cell factories" to produce industrial enzymes (Ruiz-Garcia et al, 2005; Niazi et al, 2014). Several B. subtilis strains can colonize the intestinal microvilli of the animal, support nutrition, and trigger a healthy immune system (Guo et al, 2016, 2017; Abd El-Tawab et al, 2016).…”
Section: Genes Involved In Promoting Animal Growthmentioning
confidence: 99%
“…plantarum UCMB5113 is the most effective strain against V. longisporum and also shows plant growth-promoting activity. UCMB5113 produces antibiotic compounds and bio-surfactants, which are probably involved in the bio-control properties of the bacterium (Danielsson et al, 2007;Niazi et al, 2014.). However, its BCA capacities can also act indirectly and be caused by plant defence priming (Sarosh et al, 2009).…”
Section: Bio-control Agents and Organic Soil Amendmentsmentioning
confidence: 99%